Fracture toughness assessment of a solder joint using double cantilever beam specimens - Lee, Adeline Puay Chen (2010)
Conventional assessment of solder joint reliability uses either ball shear test or solder ball pull test. The test results are reported in terms of materials strength in either shear or tensile mode, and the strength values are size-dependent. Therefore these test results are largely useful only for qualitative comparison and qualification of the products. In the current effort, we aim at developing an assessment scheme for solder joint interface fracture toughness. The obtained results, in terms of critical energy release rate, predict the joint failure based on the principle of fracture mechanics. The results can be used as a materials property in the reliability design of various types of solder-ball joined packages. Double cantilever beam (DCB) specimens made of 99.9 wt% copper were selected in the current work. Eutectic Sn-37Pb solder was used to join two pieces of the copper plates with controlled solder thickness. The test record showed steady propagation of the crack along the solder/copper interface, which verifies the viability of such a testing scheme. Interface fracture toughness for as-joined, extensively-reflowed and thermally aged samples has been measured. Both the reflow treatment and the thermal aging lead to degradation of solder joint fracture resistance. To understand the degradation, fractographic analysis by scanning electron microscopy (SEM) has been carried out from both top and cross-sectional views of the fractured surfaces.